Multi-Symplectic Fourier Pseudospectral Method for the Kawahara Equation (Communications in Computational Physics, 2014)
In this paper, we derive a multi-symplectic Fourier pseudospectral schemefor the Kawahara equation with special attention to the relationship between the spectral differentiation matrix and discrete Fourier transform. The relationship is crucial forimplementing the scheme efficiently. By using the relationship, we can apply the FastFourier transform to solve the Kawahara equation. The effectiveness of the proposedmethods will be demonstrated by a number of numerical examples. The numericalresults also confirm that the global energy and momentum are well preserved.